CHILDREN’S PRAYER AS A METAPHYSICAL LIMIT OF A.P. CHEKHOV’S EARLY PROSE IN THE SHORT STORY “VANKA” - Abdullaeva Ikbola Mokhirovna (Modern American Journals, 2026)
This research investigates the transformation of the axiological vector in the works of A.P. Chekhov between 1880 and 1887. The study focuses on the transition from a poetics of satirical deconstruction to the establishment of an existential verticality. Through a detailed analysis of the short story “Vanka” (1886), the author argues that the protagonist’s undeliverable letter functions as a phenomenon of metaphysical prayer. This act marks a pivotal shift in Chekhov’s anthropology, where human subjecthood is asserted through a transcendent impulse that overcomes the brutality of profane reality.
Keywords: A.P. Chekhov, “Vanka”, Metaphysical Prayer, Existential Ethics, Axiological Vector, Poetics of Childhood.